Persepsi Keberlangsungan Usaha Menurut Pelaku Usaha Kecil Menengah pada Saat Pandemi Covid-19 - Andre Veri Irawan; Ajeng Nawangsari (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
Purpose: This study aims to understand the meaning of business continuity according to small and medium business actors in Wonocolo, especially during the Covid-19 pandemic.Method: The research method used in this study is multiparadigm research with an interpretive paradigm. The analytical tool uses transcendental phenomenology by collecting data through in-dept interviews and observation. The data used is primary data sourced from three informants. Then the data were analyzed using a set of transcendental phenomenological methods. Among other things, analyzed noema, epoch, noesis, intentional analysis, and cidetic reduction and finally discussing the result of the interview data.Results: The findings of the study are based on the results of an analysis that mentality, product quality, faith and submission to God are part of the principles of business continuity according to small and medium business actors.Implications: The existence of this research is expected to broaden the way of thinking in running a business and perceiving business continuity for small and medium business actors by not only being oriented towards material aspects in the form of profit or profit but there are other things that also need to be considered, such as incorporating spiritual values (inner). into managing their business so that these small and medium business actors can survive well in difficult times such as during a crisis, one of which is a pandemic.Novelty: This research brings a new perspective on how the perception of business continuity during a crisis is interpreted by revealing the deepest awareness of the informants about the meaning of going concern.